The shattered helmet - Dixon, Franklin W. (New York, Grosset & Dunlap, 1973)
The Hardy brothers' visiting Greek pen pal enlists their help in searching for a priceless ancient Greek helmet loaned to and lost by a Hollywood movie company years before.
Keywords: Mystery and detective stories